Adaptation of Stanford Presenteeism Scale-6 in Indonesia - Tanama, Fery Alfaro; Adi, Nuri Purwito; Werdhani, Retno Asti; Herqutanto, Herqutanto (Occupational and Environmental Medicine Journal of Indonesia, 2024)
Background: Presenteeism has been identified to cause productivity loss more than 50% greater than absenteeism. Currently in Indonesia there are no standardized tools to assess presenteeism among workers. Therefore, we intended to adapt and validate SPS-6 in Indonesia. Methods: This is a cross-sectional study with cross-cultural adaptation refers to the ISPOR method, with a validity and reliability statistical test. Total respondents were 112 white-collars workers. Inter-item correlation was used for validity test and Cronbach’s Alpha was used for reliability test. Results: Cross-cultural adaptation of SPS-6 has been successfully done. The most significant change occurred in the explanation of the health problem definition. All item and item’s dimension were statistically significant correlated with total score. Cronbach’s alpha of work focus dimension and psychological dimension was 0.657 and 0.646, respectively. Conclusion: The Indonesian version of the SPS-6 questionnaire was valid and reliable and could be used as an instrument to identify presenteeism for office workers (white collar workers) in Indonesia.